A Review of Research on Working Memory - Zhang, Yibo (International Journal of Social Sciences and Public Administration, 2025)
Working memory is a core cognitive system responsible for the temporary maintenance and manipulation of information essential for reasoning, learning, and problem solving. Research has developed multiple theoretical models, including Baddeley and Hitch’s multi-component model, Cowan’s embedded-processes framework, and Miller’s capacity limits, to explain its structure and constraints. Behavioral paradigms, neuroscience techniques such as fMRI, EEG, and TMS, and animal models have advanced understanding of the neural mechanisms underlying working memory. Working memory impairments are closely linked to neurological and psychiatric disorders, and interventions such as cognitive training and brain stimulation show promise for improving working memory function.